2017
DOI: 10.1016/j.afos.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Antiresorptive agent-related osteonecrosis of the jaw in osteoporosis patients from Asian countries

Abstract: Bisphosphonate (BP)-associated osteonecrosis of the jaw (ONJ) was first reported in oncology patients in 2003 and subsequently in osteoporosis patients in 2004. Since oral surgical procedures, such as tooth extraction, are also considered one of the major risk factors for ONJ, there is confusion among physicians, dentists, and patients—particularly osteoporosis patients currently taking BPs—regarding the safety of remaining on therapy surrounding these procedures. Many papers about BP-related ONJ (BRONJ) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Among previous studies in osteoporosis patients in Asia, the closest value reported was 2.83 (per 1000 person-years), which was reported in the National Taiwan University study by Chiu [ 43 ]. However, remarkable differences existed in other Asian studies, with reported values ranging from 0.08 to 2.8 (per 1000 person-years) [ 16 ]. Therefore, the value obtained in our study was within a reasonable range in Asia.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Among previous studies in osteoporosis patients in Asia, the closest value reported was 2.83 (per 1000 person-years), which was reported in the National Taiwan University study by Chiu [ 43 ]. However, remarkable differences existed in other Asian studies, with reported values ranging from 0.08 to 2.8 (per 1000 person-years) [ 16 ]. Therefore, the value obtained in our study was within a reasonable range in Asia.…”
Section: Discussionmentioning
confidence: 93%
“…Risk factors for MRONJ include age [ 10 ], sex, comorbidities (diabetes mellitus [DM] [ 5 ], chronic kidney disease [CKD], anemia [ 11 ], hyperthyroidism [ 12 ], hypothyroidism, rheumatoid arthritis, periodontal disease [ 11 , 13 ]), dental treatment regimens (tooth extractions [ 11 ], ill-fitting dentures), and drugs (corticosteroid [ 14 ], antiangiogenic agents [bevacizumab and sunitinib] [ 15 ]). The incidence of MRONJ among patients using BPs injections has been reported as 2 to 15% [ 16 ]. In a survey study of more than 13,000 Kaiser Permanente members, the prevalence of MRONJ in osteoporotic patients receiving long-term oral BP therapy was reported as 0.1% (10 cases per 10,000), which increased to 0.21% (21 cases per 10,000) in patients who had been taking oral BPs for more than 4 years [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was described that the development of MRONJ in patients with osteoporosis is related to suppuration, use of bisphosphonate, tooth extraction, and anemia [ 96 ]. Others showed that dental extractions, dental implants, and apical or periodontal surgery are the main factors involved in MRONJ [ 97 ]; additional risk factors such as dental prostheses with poor adaptation, excessive chewing force, poor oral hygiene, periodontal disease, and morphological bone irregularities have been related to MRONJ [ 98 ]. These conditions are absent in children and adolescents, and the masticatory force is lower in this group, showing another protective condition against MRONJ [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, review upon jaw necrosis related to antiresorptive agent such as bisphosphonate and denosumab was impressive as it relates the occurrence of the jaw bone necrosis to the oral health, not to the antiresorptive agent itself [1] . It is the infectious oral conditions, not antiresorptive agent itself that matters in the incidence of the jaw bone necrosis with the patients on bisphosphonate as an antiresorptive therapy, according to the authors.…”
mentioning
confidence: 99%